Is Hypereosinophilia A Sign of Underlying Tuberculosis? A Case Report and Review of Literature - Basit Momin, Majed Abdul; Ingle, Abhijeet; Krishna Reddy, G Vamshi; Dev Singh, R Rahul; Hassan, Rubina (International Journal of Human and Health Sciences (IJHHS), 2023)
Eosinophilia is a common haematological problem that we see in our clinical practice. It is unusual to find hypereosinophilia at the onset of inguinal tuberculous lymphadenitis and hepatic non-granulomatous eosinophilic necrosis. We present the case of a 67-yearold man who complained of a dry cough for three months and a fever for one month. The right inguinal lymph node was palpable on clinical examination and initial haematological investigation revealed marked hypereosinophilia, mimicking myeloproliferative disorder. A thorough imaging workup revealed extensive thoracic lymphadenopathy as well as multiple liver lesions. Further liver mass core biopsy revealed hepatic, non-granulomatous necrosis with eosinophilic infiltration, whereas excision biopsy of inguinal lymph node revealed granulomatous inflammation with positive acid-fast bacili on histopathological examination. The patient responded to anti-tubercular treatment with steroids and hydroxyurea. The case emphasizes the association of eosinophilia in tuberculosis with tendency to forming mass lesions in liver and also the role of eosinophilic proteins in tissue injury. International Journal of Human and Health Sciences Vol. 07 No. 03 Jul’23 Page: 262-266